2021
DOI: 10.1111/mpp.13077
|View full text |Cite
|
Sign up to set email alerts
|

Rootstock influences the effect of grapevine leafroll‐associated viruses on berry development and metabolism via abscisic acid signalling

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 161 publications
(216 reference statements)
1
24
0
Order By: Relevance
“…Latter authors observed the modulation of genes related to pathogen detection, for example NBS-LRR genes that confer resistance to powdery and downy mildew (DM) in grapevine ( Riaz et al, 2011 ; Zini et al, 2019 ), as well as abscisic acid (ABA) signaling, phenylpropanoid biosynthesis, and cytoskeleton remodeling similar to previous studies of Vega et al (2011) and Ghaffari et al (2020) . Interestingly the increase of ABA abundance in GLRD-infected berries ( Vondras et al, 2021 ) was different than that observed for red blotch virus-infected berries, in which ABA abundance and NCED expression decrease in infected berries after véraison ( Blanco-Ulate et al, 2017 ).…”
Section: Virus Infectionsmentioning
confidence: 66%
See 2 more Smart Citations
“…Latter authors observed the modulation of genes related to pathogen detection, for example NBS-LRR genes that confer resistance to powdery and downy mildew (DM) in grapevine ( Riaz et al, 2011 ; Zini et al, 2019 ), as well as abscisic acid (ABA) signaling, phenylpropanoid biosynthesis, and cytoskeleton remodeling similar to previous studies of Vega et al (2011) and Ghaffari et al (2020) . Interestingly the increase of ABA abundance in GLRD-infected berries ( Vondras et al, 2021 ) was different than that observed for red blotch virus-infected berries, in which ABA abundance and NCED expression decrease in infected berries after véraison ( Blanco-Ulate et al, 2017 ).…”
Section: Virus Infectionsmentioning
confidence: 66%
“…It also delays fruit ripening, reduces sugar accumulation, and impairs fruit pigmentation ( Guidoni et al, 1997 ; Maree et al, 2013 ; Naidu et al, 2014 , 2015 ; Alabi et al, 2016 ). Decreases in anthocyanin and total flavonoid concentrations due to GLRD infections were related to the downregulation of anthocyanin-related transcripts, such as VvUFGT , VvMYABA1, and other phenylpropanoid genes, such as VvCHS , VvFLS1, and VvMYAPA1 ( Vega et al, 2011 ; Vondras et al, 2021 ). Vega et al (2011) also observed a viral repression of sugar transporters, which translated to lower sugar concentration in grapes.…”
Section: Virus Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…vinifera cv. Cabernet Franc FPS clone 04 genome was assembled and scaffolded with PacBio reads and Dovetail HiC data (48). Muscadinia rotundifolia cv.…”
Section: Methodsmentioning
confidence: 99%
“…Cabernet Franc cl. 04 (36) and Muscadinia rotundifolia cv. Trayshed (37) pseudomolecule assemblies are available at www.grapegenomics.com.…”
Section: Data Availabilitymentioning
confidence: 99%